PEMANFAATAN DANA PROGRAM KELUARGA HARAPAN (PKH) TERHADAP MOTIVASI BELAJAR SISWA DI KECAMATAN KUTA BARO KABUPATEN ACEH BESAR - Miftahul Jannah; Amiruddin Amiruddin; Nazaruddin Nazaruddin (Jurnal Ilmiah Mahasiswa Pendidikan Ekonomi, 2019)
This research entitled "Utilization of Family Hope Funds Program TowardStudents Learning Motivation in Kuta Baro District, Aceh Besar District". Theresearch problems in this study are (1) How is the utilization of Family Hope Funds Programs (PKH) by families of beneficiary students in Kuta Baro District, Aceh Besar Regency? (2) what are the influences of the utilization of PKH funds on students motivation in Kuta Baro District, Aceh Besar Regency?. This study aims to find out the utilization of Family Hope Funds Programs (PKH) by the families of beneficiary students and to find out the effect of the utilization of Hope Family Funds Program (PKH) on students motivation in Kuta Baro District, Aceh Besar Regency. The method used in this research is a quantitative method and descriptive research type. The research location is in Kuta Baro District, Aceh Besar Regency. The population in this study are all junior and senior high school students who receive the Family Hope Funds Program (PKH) assistance in Kuta Baro District, which amounted to 560 students. Samples in this study were taken for 84 students and parents of students beneficiaries of the Family Hope Funds Program (PKH) located in 4 schools in Kuta Baro District, Aceh Besar Regency, namely: SMAN 1 Kuta Baro, SMAN 2 Kuta Baro, SMP N 1 Kuta Baro and SMP N 2 Kuta Baro. The method of data collection was done by using the documentation and questionnaire methods. The data of this study were analyzed using the simple linear regression analysis techniques, the coefficient of determination. And to test the hypothesis was used the t test statistic test. The results of the analysis and data processing showed that there was a significant influence between the utilization of the Family Hope Funds Program (PKH) on student motivation at 36.5%. To prove this influence, a hypothesis test was done and obtained a value of tcount t table (82) , which was 6.87 1.66, which meant that Ha was accepted at a significant level of 5% and dk = 82.Therefore, the utilization of Family Hope Funds Program (PKH) influenced students motivation in Kuta Baro District, Aceh Besar District.